If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(9 + 3x) = 3 + -6x (9 * 5 + 3x * 5) = 3 + -6x (45 + 15x) = 3 + -6x Solving 45 + 15x = 3 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 45 + 15x + 6x = 3 + -6x + 6x Combine like terms: 15x + 6x = 21x 45 + 21x = 3 + -6x + 6x Combine like terms: -6x + 6x = 0 45 + 21x = 3 + 0 45 + 21x = 3 Add '-45' to each side of the equation. 45 + -45 + 21x = 3 + -45 Combine like terms: 45 + -45 = 0 0 + 21x = 3 + -45 21x = 3 + -45 Combine like terms: 3 + -45 = -42 21x = -42 Divide each side by '21'. x = -2 Simplifying x = -2
| -0.6x+1.45=-0.4x+6.65 | | Z=4(a+5b)+7(3a+b) | | 100[x+3]=450-50x | | .50x^2-12=18 | | C-4=27 | | 5x+20=4y | | 2(3x+9)=-16+22 | | 3.7+0.5b+2.9b=-10.92 | | 0.33x^2-5=36 | | 20x+250=500 | | 20+x(-4)=44 | | 5n+20n=5[n+20] | | 20x-250=500 | | 4x-2x+3=100 | | 26=2(x-6)(x+3) | | 102=7y | | 4x^2-50=6 | | x-2x+9=0 | | r^2-6r-72=0 | | Q=0.5c+0.5d*d | | 6n+17=19 | | 2(q-0.1)=3(0.3-q) | | 4(2a+7)= | | 1(x-6)=3x | | 3b-2a=4 | | 2.5x+0.50=4 | | 290+77(x)=1676 | | 15x-2=15x-1 | | 8(x+1)=56 | | 18x-4=32 | | x^2-25=-5 | | 1.8t=9.18 |